Effect of Cooperative Learning Model Type Course Review Horay (CRH) on Elementary Students’ Learning Outcome in Social Subject - Marhadi, Hendri; N, Lazim; Erlisnawati, Erlisnawati; Purnama, Nia (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This study aims to examine the effect of cooperative learning model type course review horay (CRH) on elementary students learning outcome. The design of this research is experimental and conducted by 35 students. The results of this study after applying cooperative learning model typecourse review horay (CRH) the average score of students the average score of students on the basic score of 68.4 experienced an increase in the first cycle of 79.29 and in the second cycle got 90.58. With the increase of learning outcomes in the first cycle of 15.91% and on the second cycle of 32.41%. With the increase of learning outcomes in the first cycle of 15.91% and on the second cycle of 32.41. Thus, implementation cooperative learning model type course review hooray can effectively promote elementary students’ learning outcome in social subject.